Some Aspects of Russia's Integration into the European Transport System - Sergey Shlikhter (Promet - Traffic&Transportation, 1970)
While the Russian space has extended over ve1y large paJtsof Eurasia its economic consistency and growth was primarilydepending on the development of a huge railway net. It was alsoparamount for the strength of the Soviet empire. Technicallyand administratively, however, the transport system has beenisolated from its neighbours. This may prove disadvantageousin the future when much closer economic cooperation in particularwith Europe will gain in importance. To satisfy theseneeds, a dual transport system - Russian railways plus transcontinentalmaglev lines, may be the key solution.